Physical soil properties in crop-livestock integration system in Humic Cambisol (Revista de Ciências Agroveterinárias, 2016)
In integrated crop-livestock systems under a no-tillage system, the action of animal trampling can influence the physical properties of the soil, depending on the intensity of grazing and stocking rate. This study aimed to evaluate the physical properties of a Humic Cambisol, under an integrated crop-livestock system submitted to different grazing intensities of lactating cows in the city of Lages, SC. The treatments constituted three forage masses of winter pasture (low, medium and high), and a control area, with no grazing (no grazing), oat and ryegrass consortium was used, then the density, hydraulic properties of the soil, organic matter content, aggregation and soil penetration resistance were evaluated. Generally the animal trampling had no significant influence on physical properties, the dynamics of water and the contents of soil organic matter. The macroporosity conditions, as well as high resistance to penetration, principally in conditions of low moisture, prove that the Humic Cambisol of the franc silty clay texture provides a constraint physical problem.
Keywords: No-tillage system; soil management; soil cover; soil organic matter.